2007
DOI: 10.1085/jgp.200609575
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ Oscillations, a Potential Pacemaking Mechanism in Early Embryonic Heart Cells

Abstract: Early (E9.5–E11.5) embryonic heart cells beat spontaneously, even though the adult pacemaking mechanisms are not yet fully established. Here we show that in isolated murine early embryonic cardiomyocytes periodic oscillations of cytosolic Ca2+ occur and that these induce contractions. The Ca2+ oscillations originate from the sarcoplasmic reticulum and are dependent on the IP3 and the ryanodine receptor. The Ca2+ oscillations activate the Na+-Ca2+ exchanger, giving rise to subthreshold depolarizations of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 47 publications
(66 reference statements)
12
96
0
1
Order By: Relevance
“…However, repetitive Ca 2+ signals and rhythmic contractions occur in these RyR-deficient animals at E7−9.5 [87,88]. In addition, the Ca 2+ signals in young embryonic heart cells are insensitive to experimental maneuvers that inhibit voltage-activated Ca 2+ channels or Na + /Ca 2+ exchange, but are affected by agents that deplete intracellular Ca 2+ stores [89] (but see [90] for an alternative view). Taken together, these data indicate that periodic Ca 2+ release from intracellular stores occurs in young embryonic heart cells, and that the channels involved are not RyRs.…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, repetitive Ca 2+ signals and rhythmic contractions occur in these RyR-deficient animals at E7−9.5 [87,88]. In addition, the Ca 2+ signals in young embryonic heart cells are insensitive to experimental maneuvers that inhibit voltage-activated Ca 2+ channels or Na + /Ca 2+ exchange, but are affected by agents that deplete intracellular Ca 2+ stores [89] (but see [90] for an alternative view). Taken together, these data indicate that periodic Ca 2+ release from intracellular stores occurs in young embryonic heart cells, and that the channels involved are not RyRs.…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
“…For example, the spontaneous Ca 2+ oscillations in murine embryonic cells were sensitive to application of 2-APB (an IP 3 R antagonist [42]) [89]. Furthermore, IP 3 Rs are expressed in the inner mass of embryos at E5.5, and are clearly evident within the developing heart tube at E8.5 [91].…”
Section: Ip 3 Signaling In Cardiac Developmentmentioning
confidence: 99%
“…Calcium release and cycling via the ryanodine receptor (RyR2), the sarcoplasmic reticulum calcium ATPase (SERCA2), the sodium calcium exchanger (NCX), and associated regulatory proteins play an essential role in pacemaker automaticity (20)(21)(22)(23). Deletion of Ryr2 or Ncx1 leads to early embryonic lethality and substantial impairment in pacemaker function (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…Synchronized states in SPCO models map onto steady-state wave fronts of our stochastic model. We note that embryonic CMs spontaneously contract in periodic manner (3,4). In the beating embryonic heart, the wave front is initiated at the atrial end of the heart tube by CMs that contract at a higher frequency.…”
Section: Discussion Mechanical Signaling Robustly Explains Strong Depmentioning
confidence: 84%
“…Although embryonic CMs beat spontaneously (3,4), they would contract with random phases in the absence of a coordinating signal. A number of studies have shown that embryonic, neonatal, and adult CMs are sensitive to mechanical cues (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%